2013
DOI: 10.1124/mol.112.083873
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Allosterically Inhibits the Proteasome

Abstract: Rapamycin is a canonical allosteric inhibitor of the mammalian tarpet of rapamycin (mTOR) kinase with immunosuppressive and proapoptotic activities. We found that in vitro rapamycin also regulates the proteasome, which is an essential intracellular protease of the ubiquitin-proteasome pathway. Rapamycin inhibits proteinase and selected peptidase activities of the catalytic core proteasome at low micromolar concentrations. Moreover, the drug interferes with binding of the 19S cap essential for processing of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…AFM imaging of the human 20S proteasomes revealed that rapamycin shifts the conformational equilibrium toward a higher abundance of the open particles (Fig. 4E) (102). We speculate that on docking to the a face, rapamycin exploits the allosteric route used by gate-opening regulatory modules.…”
Section: Allosteric Route: From the Grooves On A Face To The Gatementioning
confidence: 90%
See 4 more Smart Citations
“…AFM imaging of the human 20S proteasomes revealed that rapamycin shifts the conformational equilibrium toward a higher abundance of the open particles (Fig. 4E) (102). We speculate that on docking to the a face, rapamycin exploits the allosteric route used by gate-opening regulatory modules.…”
Section: Allosteric Route: From the Grooves On A Face To The Gatementioning
confidence: 90%
“…At high nanomolar concentrations of rapamycin, post-acidic cleavages are inhibited by a noncompetitive mechanism. At low micromolar concentrations, the ChT-L peptidase is strongly inhibited, while the T-L peptidase activity is increased twofold (102). Interestingly, rapamycin abolishes activation of the 20S core by 19S complex or by peptides containing the HbYX motif.…”
Section: Allosteric Route: From the Grooves On A Face To The Gatementioning
confidence: 97%
See 3 more Smart Citations